A Middle Devensian woolly rhinoceros (Coelodonta antiquitatis) from Whitemoor Haye Quarry, Staffordshire (UK): palaeoenvironmental context and significance. (18th December 2012) - Schreve, Danielle; Howard, Andy; Currant, Andrew; Brooks, Stephen; Buteux, Simon; Coope, Russell; Crocker, Barnaby; Field, Michael; Greenwood, Malcolm; Greig, James; Toms, Phillip
Abstract This paper reports the discovery of a rare partial skeleton of a woolly rhinoceros (Coelodonta antiquitatis Blumenbach, 1799) and associated fauna from a low Pleistocene terrace of the River Tame at Whitemoor Haye, Staffordshire, UK. A study of the sedimentary deposits around the rhino skeleton and associated organic‐rich clasts containing pollen, plant and arthropod remains suggests that the animal was rapidly buried on a braided river floodplain surrounded by a predominantly treeless, herb‐rich grassland. Highlights of the study include the oldest British chironomid record published to date and novel analysis of the palaeoflow regime using caddisfly remains. For the first time, comparative calculations of coleopteran and chironomid palaeotemperatures have been made on the same samples, suggesting a mean July temperature of 8–11 °C and a mean December temperature of between −22 and −16 °C. Radiocarbon age estimates on skeletal material, supported by optically stimulated luminescence ages from surrounding sediments, indicate that the rhino lived around 41–43 k cal a BP. The combined geochronological, stratigraphic and palaeoenvironmental evidence places the assemblage firmly within the Middle Devensian (Marine Oxygen Isotope Stage 3). This would agree with other regional evidence for the timing of aggradation for the lowest terrace of the Trent and its tributary systems. Copyright © 2012 John Wiley & Sons, Ltd.